Técnicas conductuales para prevenir la dependencia a las redes sociales en los estudiantes de décimo año paralelo a, de la escuela de educación general básica José Ingenieros, 2018-2019. - Ordoñez Hidalgo, Leydi Marianela (2019)
The social networks use in adolescence is considered as a psychosocial problem that affects their development. This issue led us to work on the topic: Behavioral techniques to prevent dependence on social networks, with the general aim of: Implementing a plan based on behavioral techniques to prevent social networks dependence in students of the tenth year parallel "A" from the José Engineers school. Descriptive study, of cross section, pre-experimental design; based on scientific theoretical methods. The Addiction Scale for Social Networks was applied in a sample of 26 students. The results, initial (pretest) 50% of students are obsessed with social networks, likewise 46.15% indicate lack of control in the use of networks, and 53.85% make excessive use of social networks. Subsequent (post-test) results after the intervention achieved low levels in percentages of 53.85%; 57.69%; 61.54% for obsession, lack of control and excessive use of social networks respectively. The results of the application of the Plan statistically (linear correlation of Karl Pearson (r), in the six workshops for Obsession with social networks, Lack of control in the use of social networks, Excessive use of social networks, values are reached of correlation r (xy) between = 0, 80 ar (xy) 0.87, which means a high positive correlation, concluding that the behavioral techniques are effective, upon reaching a high positive correlation, validated to prevent dependence on excessive use of social networks